A Hybrid Immersed Boundary-Lattice Boltzmann Method for Simulation of Viscoelastic Fluid Flows Interaction with Complex Boundaries (Communications in Computational Physics, 2021)
In this study, a numerical technique based on the Lattice Boltzmann methodis presented to model viscoelastic fluid interaction with complex boundaries which arecommonly seen in biological systems and industrial practices. In order to accomplishnumerical simulation of viscoelastic fluid flows, the Newtonian part of the momentumequations is solved by the Lattice Boltzmann Method (LBM) and the divergence of theelastic tensor, which is solved by the finite difference method, is added as a force termto the governing equations. The fluid-structure interaction forces are implementedthrough the Immersed Boundary Method (IBM). The numerical approach is validatedfor Newtonian and viscoelastic fluid flows in a straight channel, a four-roll mill geometry as well as flow over a stationary and rotating circular cylinder. Then, a numericalsimulation of Oldroyd-B fluid flow around a confined elliptical cylinder with differentaspect ratios is carried out for the first time. Finally, the present numerical approachis used to simulate a biological problem which is the mucociliary transport process ofhuman respiratory system. The present numerical results are compared with appropriate analytical, numerical and experimental results obtained from the literature.
Keywords: Lattice Boltzmann method; immersed boundary method; viscoelastic fluid; complex boundaries; mucociliary transport.